Advancing the Study of Positive Psychology: The Use of a Multifaceted Structure of Mindfulness for Development - Phan, Huy P.; Ngu, Bing H.; Chen, Si Chi; Wu, Lijuing; Shi, Sheng-Ying; Lin, Ruey-Yih; Shih, Jen-Hwa; Wang, Hui-Wen (Frontiers in Psychology, 2020)
It is an interesting premise to consider the use of mindfulness from an Eastern perspective to guide our theoretical understanding and appreciation of positive psychology. Positive psychology, as a distinctive paradigm, focuses on the remedy of pathologies and, by contrast, the promotion of positive experiences and conditions in life (Pawelski 2016). Indeed, from our point of view, positive psychology provides grounding for the establishment of policies, programs, and pedagogical practices that could facilitate the enrichment of subjective well-being (e.g., feeling good about oneself). In the context of academic learning, for example, educators have used positive psychology to foster the achievement and self-fulfillment of optimal best practice (Phan, Ngu et al. 2019). An appreciation for positive psychology is paramount. Positive psychology, in its simplistic form, may provide evidence and insightful understanding into the proactivity of human agency (Seligman 1999, Seligman and Csíkszentmihályi 2000). How do we emphasize and encourage the saliency of positive psychology? In our extensive research development, we have addressed this topical theme of positive psychology by making reference to a related inquiry – namely, the enactment of the process of optimization (Fraillon 2004, Phan, Ngu et al. 2017, Phan, Ngu et al. 2019), which would result in the achievement of optimal best. In the present article, we engage in philosophical psychology and personal-based teaching and reasoning to consider mindfulness as another possible pathway. In this analysis, we posit that mindfulness, from the perspectives of Confucianism and Buddhism, could serve to enhance meaningful understanding and appreciation for the study of positive psychology.